2018
DOI: 10.1111/gbb.12514
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of social behavior and dominance status by chronic pain in mice

Abstract: The potential influence of pain on social behavior in laboratory animals has rarely been evaluated. Using a new assay of social behavior, the tube co-occupancy test (TCOT), we assess propinquity-the tendency to maintain close physical proximity-in mice exposed to pain using subcutaneous zymosan or spared nerve injury as noxious stimuli. Our previous experience with the TCOT showed that outbred mouse sibling dyads show higher levels of tube co-occupancy than stranger dyads. We find here that long-lasting pain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…On the other hand, dominance relationships can be altered by chronic pain. It has been reported that chronic constriction injury in rats and SNI in mice leads to loss of dominance in the different dominance experiment (Monassi et al, 2003; Tansley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, dominance relationships can be altered by chronic pain. It has been reported that chronic constriction injury in rats and SNI in mice leads to loss of dominance in the different dominance experiment (Monassi et al, 2003; Tansley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect of the pain on social factors seems to be more related to the duration of pain before testing. It has been shown that short‐lasting pain did not significantly affect propinquity behavior on the tube co‐occupancy test, but long‐lasting pain produced a significant change in the propinquity behavior in mice (Tansley et al, 2019). Also, Palazzo et al (2016) reported that 1 month after spared nerve injury (SNI) in mice, the animals in pain exhibited impairment in both their sociability as well as social novelty preference in the three‐chambered test.…”
Section: Discussionmentioning
confidence: 99%
“…Six female mice 8 to 12 weeks old were used for the experiment (3 for SNI group, 3 for Sham group). We performed the experiments on female mice because female mice are less aggressive to other female mice than male mice [ 76 ]. We considered this stress as a confounder in our experiments that might alters the gut microbial diversity and composition.…”
Section: Methodsmentioning
confidence: 99%
“…Six female mice 8 to 12 weeks old were used for the experiment (3 for SNI group, 3 for Sham group). We performed the experiments on female mice because female mice are less aggressive to other female mice than male mice (Tansley et al, 2019). We considered this stress as a confounder in our experiments that might alters the gut microbial diversity and composition.…”
Section: Animal Preparationmentioning
confidence: 99%